The response of Teso zebu milking stock to moderate levels of supplementary feeding - Joblin, A.D.H. (1966)
A 2-year trial is described where locally produced rations, fed to Zebu (Nkedi)cattle as a supplement to normal grazing, were tested for their effects on milk yield and cattle condition. The rations used were a cooked mixture of eight parts of sorghum to two parts of cottonseed, cooked cassava and raw cassava, fed at the rate of 12 lb of wet matter per gallon of morning milk, and compared with an unsuplemented control group. No effects were found on milk yield, suckling calf growth rates of lactation length, but all rations maintained the milking cattle in better condition. Part of this condition effect appeared to be carried through to the following calving interval. A second trial is also described where a sorghum/ cottonseed cake ration was tested for its effects on growth rate in young stock. The response was again disappointing. It is concluded that moderately well managed local pastures are capable of supplying all the necessary nutrients for the local cattle to realize their present genetic milk potential of approximately one gallon a day.